Implementasi Akad Syariah Di Lembaga Keuangan Syariah: Tantangan, Regulasi, Dan Strategi Peningkatan Literasi Keuangan Syariah - Hidayat Harahap, Taufik (YUDHISTIRA : Jurnal Yurisprudensi, Hukum dan Peradilan, 2023)
This study aims to analyze the implementation of Sharia contracts in Islamic financial institutions and the challenges encountered in practice. Additionally, it evaluates the effectiveness of regulations enforced by the Financial Services Authority (OJK) and the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) in ensuring compliance with Sharia contracts. Furthermore, this study examines the impact of public understanding on compliance with Sharia transactions to formulate strategies for enhancing Islamic financial literacy. This research employs a qualitative literature study approach by analyzing various secondary sources, including scientific journals, books, OJK regulations, DSN-MUI fatwas, and annual reports of Islamic financial institutions. The data is analyzed descriptively and qualitatively by categorizing information based on the implementation of Sharia contracts, regulatory effectiveness, and the impact of financial literacy on compliance with transactions. The findings indicate that although the regulations implemented by OJK and DSN-MUI are comprehensive, challenges remain in the application of Sharia contracts, such as limited public understanding of Sharia principles and variations in contract implementation by financial institutions. Therefore, a more effective strategy for improving Islamic financial literacy is necessary to enhance compliance with Sharia transactions.